Laryngeal mask vs. laryngeal tube trial in paediatric patients (LaMaTuPe): a single-blinded, open-label, randomised-controlled trial - Katzenschlager, Stephan; Mohr, Stefan; Kaltschmidt, Nikolai; Peterstorfer, Franziska; Weilbacher, Frank; Günther, Patrick; Ries, Markus; Weigand, Markus A.; Popp, Erik (European journal of emergency medicine, 2025)
Background: In hypoxemic children with difficult airway, or for minor elective procedures, the use of a supraglottic airway device may be preferred to endotracheal intubation, whether with a laryngeal mask or laryngeal tube. Second-generation laryngeal masks may offer a better safety profile. Whether they should be preferred to laryngeal tubes is unknown. This study aimed to compare the efficacy and safety of second-generation laryngeal masks and laryngeal tubes in children. - Methods: This randomised-controlled trial was conducted in a single university hospital in children <18 years undergoing elective anaesthesia in urology, minor paediatric surgery and gynaecology. Patients were 1 : 1 randomised to the laryngeal mask or laryngeal tube group. Children were allocated a second-generation laryngeal tube or a second-generation laryngeal mask as the primary airway device. The primary endpoint was insertion time. Secondary endpoints included first-attempt success, overall success and complications, which included hypoxia (SpO2 < 90%), laryngospasm, bronchospasm, aspiration and bleeding. - Results: In total, 135 patients were randomised, with 61 allocated to the laryngeal tube and 74 to the laryngeal mask group, with a median age of 5.4 and 4.9 years, respectively. Median insertion time was significantly longer in the laryngeal tube group (37 vs. 31 s; difference of medians: 6.0 s; 95% confidence interval: 0.0-13.0). The laryngeal tube had a significantly lower first-attempt (41.0%) and overall success rate (45.9%) than the laryngeal mask (90.5% and 97.3%, respectively). Those allocated to the laryngeal tube group had a higher ratio of complications (27.8%) compared to the laryngeal mask group (2.7%). - Conclusion: This randomised-controlled trial reported that in children undergoing elective anaesthesia, the use of a laryngeal tube was associated with a longer insertion time.